Stacking engineering induced Z-scheme MoSSe/WSSe heterostructure for photocatalytic water splitting - Ren, Longjun; Liu, Zongfa; Ma, Zhen; Ren, Kai; Cui, Zhen; Mu, Weihua (Frontiers in Chemistry, 2024)
Stacking engineering is a popular method to tune the performance of two-dimensional materials for advanced applications. In this work, Jansu MoSSe and WSSe monolayers are constructed as a van der Waals (vdWs) heterostructure by different stacking configurations. Using first-principle calculations, all the relaxed stacking configurations of the MoSSe/WSSe heterostructure present semiconductor properties while the direct type-II band structure can be obtained. Importantly, the Z-scheme charge transfer mode also can be addressed by band alignment, which shows the MoSSe/WSSe heterostructure is an efficient potential photocatalyst for water splitting. In addition, the built-in electric field of the MoSSe/WSSe vdWs heterostructure can be enhanced by the S–Se interface due to further asymmetric structures, which also results in considerable charge transfer comparing with the MoSSe/WSSe vdWs heterostructure built by the S–S interface. Furthermore, the excellent optical performances of the MoSSe/WSSe heterostructure with different stacking configurations are obtained. Our results provide a theoretical guidance for the design and control of the two-dimensional heterostructure as photocatalysts through structural stacking.